Unveiling the impact of high-involvement work practices on team creativity: Exploring the interplay of team reflexivity and work demand attributes - Abdul Waheed; Zhu Yongyue; Salma Waheed; Shahbaz Hussain (PLoS ONE, 2025)
This study aims to investigate the association between high-involvement work practices (HIWPs) and team creative performance (TCP) in Pakistan’s hospitality industry. Moreover, the mediating role of team reflexivity (TR) and moderating role of work demand elements workload (WL) and physical work environment (PWE) have also been studied by introducing cognitive workload theory (CWT) in the TCP context. The data were collected from 408 hotel industry employees through a structured questionnaire. The data was analyzed using different statistical techniques including factor analysis, correlation and structure equation modeling, and slope analysis. Results indicate a successful moderation between HIWPs (power, information, and reward) and TR with WL and PWE. Moreover, the results of this study suggest that team reflexivity partly mediates the association between the HIWP and TCP. Results also provide evidence of cognitive workload theory in this study. Considering the results, it is mandatorily recommended to emphasize more on the work demand in the hotel industry. HIWPs should be promoted to increase TCP.